The IOC manual of emergency sports medicine - McDonagh, David O'Sullivan; Zideman, David A. (Wiley Blackwell, 2015)
The Manual focuses on the fieldside diagnosis and treatment of severe injuries and illnesses that can present at a sports event. It concentrates on basic diagnostic skills and treatment modalities as the sports physician has often limited diagnostic and treatment facilities available. Each chapter concentrates on an illness or anatomical injury and offers a structured diagnostic and therapeutic approach in this difficult pre-hospital environment. The chapters explain what problems are to be expected with specific conditions as well as which treatment plan should be implemented and how to evaluate and reassess those plans.